Optimal mesh design methodology considering geometric parameters for rock fragmentation in open-pit mining in the Southern Andes of Peru - Zamora-Paredes, V. (2020)
Blasting is one of the most important stages in the productive process of a mine due to its direct impact on rock fragmentation, which determines the degree of productivity of operations and the extraction costs generated. In this scenario, an optimized methodology is presented for designing blasting meshes by using mathematical models that help calculate the geometric parameters of a blasting mesh, such as burden, considering the variables of the rock mass and the type of explosive to measure its impact on rock fragmentation and loading productivity (tons/hour). The main advantage of this method is the reliability of the design, which takes into account a greater number of variables that influence fragmentation and uses the principle of distribution and amount of energy in an optimal way. The results obtained in the case of application show that a change in design (2.7 x 2.7 square mesh to 2.2 x 2.5 triangular mesh) reduces P80 by 65%, from 17 to 6 inches, approximately. Additionally, the results show that greater operational efficiency was achieved by increasing excavator productivity by approximately 15.6%.